A pilot study on measuring organisational culture in Vietnamese corporations in light of task and relationship orientations. (22nd August 2019) - Tran, Quan Hoang Nguyen
In this global and international world, organisational culture is a topic often inspected. This research attempts to find out what is the main characteristic of organisational culture in Vietnamese corporations. In total, 276 Vietnamese working adults in two regions in Vietnam participated. The findings from the survey data display that while task orientation is the common organisational culture in current Vietnamese companies, negative attitudes are surprising discovered. Implications are explained for further Vietnamese superiors and subordinates so that they might cooperate effectively in the future.